Situation Analysis and Needs Assessment Report for My Loi village and Ha Tinh province, Viet Nam - Le VH; Duong, Minth Tuan; Simelton, Elisabeth; Ferrer, Alice J.; Bui Tan Yen; Sebastian, Leocadio S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
My Loi village is located in the uplands of Ky Son commune, Ky Anh district, Ha Tinh province on the north central coast of Viet Nam. In 2014, it was chosen as a site for Climate-Smart Village because of its exposure to multiple extreme weather events (temperature and water stress, storm and typhoon) and the potential for climate-smart solutions. The purpose of situation analysis and needs assessment was to understand the current situation at the village and province levels, on a number of issues, including food security and natural resources management, and to identify and prioritize the needs for My Loi to develop agriculture and livelihoods in synergy with climate adaptation and mitigation interventions. Data collection was conducted in October 2014 alongside a Village Baseline Study. The findings were shared during a feedback meeting in December 2014. The major findings for My Loi Village included: 1) main livelihood sources are in forestry (140 ha acacia and eucalyptus planted in near 200 ha) and rainfed agriculture (55 ha, paddy rice, peanut, maize, green bean, and sweet potato); 2) main constraints for production are water scarcity and poor soil quality; 3) livestock was promoted to improve livelihood diversification; Low investment capital and diseases are the households’ main challenges for expansion from an average of 1-2 cows per household. Larger herds could open up opportunities for biogas production. Feed sources, however, are unclear. The villagers identified 21 stakeholders active within food security (the majority), food crisis and natural resource management. The village experienced temporary periods of food insecurity during natural disasters. While the main issues relating to natural resources were pollution (mining) and land degradation, there was little awareness of the potential impacts due to progressing climate variability and change. The CCAFS CSV projects, therefore, are a timely complement to help implement the province action plan and policies in response to climate change.